A Novel Instrumented Test as an Indicator of Sensorimotor Disturbances in the Lumbar Spine of Road Cyclists - Preliminary Results - Arriagada-Tarifeno, D; Cristi-Sanchez, I; Cedeno-Wolf, N; Gomez-Arias, B; Belmar-Millaquipay, N (IEEE, 2024)
This study examines the lumbar spine sensorimotor responses in recreational road cyclists using the instrumented Flexion-Relaxation (iFR) test, combined with surface electromyography (sEMG) and kinematic analysis through lower-back accelerometry. It aimed to identify sensorimotor alterations in the lumbar spine pre- and post- prolonged cycling (1 hour) due to the maintained spinal flexion position and cyclic movement of the lower extremity that is transmitted to the pelvis. The study involved 10 male cyclists, with a workload maintained between at 50% between the first ventilatory threshold (VT1 - aerobic) and second ventilatory threshold (VT2 - anaerobic) and employing advanced signal processing for data analysis. The methodology included an automatic segmentation of the iFR test using tri-axial accelerometers, and a detailed examination of muscle function through sEMG, with the iFR test revealing specific adaptation patterns and variability among cyclists. Results highlighted significant variations in muscle activity in the iFR extension phase (p - Value < 0.05) among all subjects and individual cases in which myoelectric silence is lost in the phase of maximum flexion after prolonged pedaling, indicating the iFR test s potential as a diagnostic tool for lumbar sensorimotor disturbances. This preliminary research underscores the need for further studies to explore sensorimotor adaptations in cycling, suggesting a broader application of the iFR test in sports science and rehabilitation.